PARAMETRIC STUDY OF IMPACT CHARACTERISTICS ON PRESSURE VESSEL BASED ON PUNCTURE AND API 579 FAILURE CRITERIA - Mariopi
Puncture is one of the most critical failures that may occur to pressure vessel due to the consequences such as leak of pressurized, flammable, toxic fluid and explosion that may follow. The main cause of puncture is due to impact with piercing impactor. Therefore, knowledege regarding impact characteristics of pressure vessel takes an important role as the basis to improve its puncture resistance. Impact characteristics are basis for tank car design and head shield design improvement. Parametric study is conducted in this research using ANSYS/LS-DYNA Version 11, focusing on study case “Head-on impact of LPG tank car” to study the characteristics by varying important parameters. The parameters are internal pressure, impact point(eccentricity), impactor geometry, and tank car head geometry (thickness and radius). The model is validated with the experimental impact test conducted by other researcher.[1] The impact effects are evaluated with two failure criterias, Puncture criteria and API 579- Section 8- Level 2 assessment criteria.Dynamic analysis are also conducted to predict the critical impact velocity. The results of this research show that tank car with higher internal pressure is more vulnerable to puncture than the lower one. Horizontal cylindrical impactor may puncture tank car easier than the vertical cylindrical impactor and flat impactor and it will be easier to puncture if the diameter is decreased. Higher eccentricity of impact point (closer to the tank car head edge) gives the lower energy absorbtion to impact, which means it is easier to puncture the tank car head. It is also found that by increasing the tank car head thickness to radius ratio (th/rh) may give a better puncture resistance. Parametric study by varying tank car head thickness to radius ratio (th/rh) evaluated with API 579 – Section 8- Level 2 assessment does not show a clear relationship with critical parameters (maximum energy absorbed and maximum force limited by API 579– Section 8- Level 2 assessment criteria), hence no conclusion can be given.